The Effect of Root Canal Preparation on the Development of Dentin Cracks - Salem Milani, Amin; Froughreyhani, Mohammad; Rahimi, Saeed; Asghari Jafarabadi, Mohammad; Paksefat, Sara (Iranian Endodontic Journal, 2012)
Introduction: Root fracture is not an instant phenomenon but a result of gradual development of tiny craze lines in tooth structure. Recent studies have shown that canal instrumentation has the potential to cause dentinal cracks. The purpose of this study was to evaluate and compare the formation of dentinal cracks caused by ProTaper rotary system to hand instrumentation. Materials and Methods: This in vitro study was carried out using 57 mandible incisor teeth. The teeth were decoronated. The roots were then examined to exclude cracked samples. A standard model for PDL simulation was used. The teeth were randomly divided into two experimental and one control group (n=19). The teeth in the experimental groups were prepared using hand or ProTaper Universal rotary instrumentation. The teeth in the control group were left unprepared. The teeth were then sectioned horizontally 3 and 6 mm from the apex, and the number of various dentinal defects was recorded using a dental operating microscope. The differences between groups were analyzed with Fisher’s exact test. <span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA;" lang="X-NONE">Results: The hand group demonstrated significantly more defects than the control group (P=0.001). However, there was no significant difference between the rotary compared to the control and hand groups (P>0.05). There was no significant difference between groups with regards to fracture (P>0.05). Other defects including internal, external and surface cracks were more frequent in the hand than in the control or rotary groups (P=0.02), but the difference was not significant between the rotary and control groups (P>0.05). <span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-ansi-language: EN-US;">Conclusion<span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-ansi-language: EN-US;">: Canal preparation, whether hand or rotary, produces structural defects in dentin. The ProTaper rotary system when used according to the manufacturer’s instructions, tends to produce fewer cracks and can be considered a safe preparation technique.